2016
DOI: 10.1002/adhm.201600780
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Subconjunctival Delivery of Brimonidine Tartrate for Glaucoma Treatment Using a Microspheres/Carrier System

Abstract: Core-shell polymer microspheres with poly(d,l-lactic-co-glycolic acid) core and poly(l-lactic acid) (PLLA) shell are developed for the long-term subconjunctival release of brimonidine tartrate (BT) in order to reduce intraocular pressure (IOP) in the treatment of glaucoma. The PLLA-rich shell acts as a diffusion barrier, enabling linear release of BT over an extended period of 40 d. The microspheres are encased in a porous non-degradable methacrylate-based carrier for ease of subconjunctival implantation in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…PLLA is generally considered as a biocompatible and biodegradable polymer used in many biomedical applications including scaffolds for tissue engineering and vehicles for drug delivery. [11c,20] A low residual content of organic solvent dichloromethane reported in our previous study could further improve the safety of PLLA PMs comparing to other conventional fabrication technologies . Indeed, the results in Figure a demonstrated that the relative viable cell counts were all higher than 90% in the negative control (no treatment) and various treatment groups (0.25–1.00 mg mL −1 ) at different exposure times, while those dropped to 10% or lower in the positive control group (phenol treatment), suggesting the cytocompatibility of the PLLA PMs.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…PLLA is generally considered as a biocompatible and biodegradable polymer used in many biomedical applications including scaffolds for tissue engineering and vehicles for drug delivery. [11c,20] A low residual content of organic solvent dichloromethane reported in our previous study could further improve the safety of PLLA PMs comparing to other conventional fabrication technologies . Indeed, the results in Figure a demonstrated that the relative viable cell counts were all higher than 90% in the negative control (no treatment) and various treatment groups (0.25–1.00 mg mL −1 ) at different exposure times, while those dropped to 10% or lower in the positive control group (phenol treatment), suggesting the cytocompatibility of the PLLA PMs.…”
mentioning
confidence: 71%
“…Polymers are highly advantageous as carriers for inhalation delivery because of their ability to carry a high payload of drugs, easy drug impregnation, biocompatibility, biodegradability, and sustainability of drug/protein release from the matrix, among others. Poly‐ l ‐lactide (PLLA) is one such polymer with the aforementioned qualities and has been utilized for various biomedical applications such as drug delivery, tissue engineering, and others …”
mentioning
confidence: 99%
“…Many formulations have been developed to circumvent these problems related to the treatment with eye drops. Examples of such systems are contact lenses (Peng et al, 2012), liposomes (Abu Hashim, El‐Dahan, Yusif, Abd‐Elgawad, & Arima, 2014; Pisal, Joshi, Padamwar, Patil, & Pokharkar, 2014), microspheres (Pek, Wu, Mohamed, & Ying, 2016) and solid inserts (Shivakumar, Desai, Subhash, Ashok, & Hulakoti, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Certain drugs harness the differing lipophilicity of the cornea to their advantage for drug delivery. Latanoprost is one of the most common ocular drugs used for the treatment of glaucoma, a disease in which there is accelerated optic nerve degeneration in association with a raised IOP (Digiuni et al, ; Pek et al, ). Latanoprost is a prostaglandin analogue that reduces IOP by increasing the uveoscleral outflow, through targeting receptors near the drainage angle.…”
Section: Introductionmentioning
confidence: 99%